ANALISIS LOYALITAS PELANGGAN PT. NAIKILAH PERUSAHAAN MINANG - Harry Leo Agusta; Yenita (AKSELERASI: Jurnal Ilmiah Nasional, 2023)
The purpose of this study, namely to determine the effect of service quality, price and satisfaction on customer loyalty of PT. NPM public transport bus passengers through quantitative methods along with multiple regression analysis to test the research hypothesis, where the research output obtained is customer satisfaction significantly influenced by Service quality also has a significant influence on PT. NPM's customer loyalty. Then, customer satisfaction and customer loyalty are significantly affected by price, but customer loyalty is not affected by customer satisfaction which has a positive but very low coefficient.